Implementation Of Olympic Learning Guidance In Producing High-Aching Students In Pai Subjects In Schools - Irawan, Wahyudi Saputra; Khoiriyah; Sholihin, Imam; Himawan, Fajaruddin; Husain, Athar Abdullatif (Educational Research Center, 2026)
The implementation of tutoring for Olympiad material is an effective strategy in improving student achievement in Islamic Religious Education (PAI) subjects in schools. This study aims to analyze the process of implementing tutoring for Olympiad and its impact on improving student achievement. The research method uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that tutoring for Olympiad can improve students' learning motivation, conceptual understanding, and analytical skills, thus producing high-achieving students in the field of PAI. The implementation of BPMO tutoring in producing high-achieving students in PAI subjects, the Role of BPMO Tutoring in Producing High-Achieving Students in PAI Subjects.